2014
DOI: 10.3109/21681805.2014.884160
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and prostate cancer: a cross-sectional study of Danish men with prostate cancer before androgen deprivation therapy

Abstract: Two-thirds of patients with prostate cancer awaiting ADT had osteoporosis or reduced bone mass. Further awareness regarding osteoporosis and bone health in prostate cancer is needed. It is suggested that patients with prostate cancer undergo a DXA scan before starting ADT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…The study group consisted of 88 patients with prostate cancer awaiting initiation of androgen‐deprivation therapy (ADT) due to metastases (bone, lymph nodes, or both). The patients had been participating in two studies at Odense University Hospital, and they had undergone WBS as part of their evaluations . Relevant blood sample results were available and traditional staging had been performed.…”
Section: Methodsmentioning
confidence: 99%
“…The study group consisted of 88 patients with prostate cancer awaiting initiation of androgen‐deprivation therapy (ADT) due to metastases (bone, lymph nodes, or both). The patients had been participating in two studies at Odense University Hospital, and they had undergone WBS as part of their evaluations . Relevant blood sample results were available and traditional staging had been performed.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to controls, we found no significant differences of bone markers (OPG, OC, DPD) at baseline in primary PCa patients, instead we observed a higher prevalence of osteoporosis (33.3-53.3%) and lower spine and hip T scores. Recent studies have observed a comparable osteoporosis prevalence of up to 33-38% in hormone-naive PCa patients [29,30], suggesting further awareness of poor bone health in PCa patients and screening DXA scans prior to ADT, a recommendation which we find suitable for modern preventive medicine standards.…”
Section: Intra-group Comparisonmentioning
confidence: 84%
“…5 ♦2018 1100 with osteoporotic fractures [28] will significantly reduce the survival of PCa patients. Interestingly, there are reports that osteoporosis is more prevalent among non-metastatic PCa patients even before ADT [29,30], which suggests an imbalance between the coupling between bone formation and resorption as a possible secondary trait of PCa in the absence of external hormonal interventions. Therefore, the first objective of this study was to evaluate bone metabolism in primary PCa patients prior to any treatment intervention (surgical or pharmacological).…”
mentioning
confidence: 99%
“…Bone health is another concern in ADT, as the treatment is known to increase susceptibility to osteoporosis. A multivariate analysis of PC patients demonstrated that smoking before ADT was significantly correlated with secondary osteoporosis in PC patients (odds ratio 1.037, 95% CI 1.011-1.065) [37].…”
Section: Treatment-related Outcomesmentioning
confidence: 99%